GOVERNMENT MAKING: MEMBUAT ULANG ILMU PEMERINTAHAN - sutoro eko (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2021)
The paper provides a critical overview of the Bulaksumur School, which has pioneered and left the governmental science (GS), and the Bandung-Jatinangor School, as the mainstream school, which reorganizes the GS in the sense of public management. We present the Timoho School, which remaking GS, with the main orientation being government making (GM). First, idealistically-axiologically, GM has an ideological-philosophical basis on populism which aims to achieve justice. Second, GM thinks about how the government and parliament act politically and legally with the constitution, legislation, and regulations, not only for ordering the state but for changing the state, which contributes to the transformation of the people into citizens. Third, GM is a body of GS knowledge that has a monodisciplinary basis, is able to produce theories of government, and uses various governmental perspectives to describe, understand, and explain the phenomena of people's lives outside the realm of the office. Fourth, government making distinguishes GS from political science which speaks of state making, and public administration which speaks of policymaking. The relationship between government and state is the entry point for GS’s attention. Fifth, GS’s knowledge bodies can be formed and enriched with five major concepts: government, governing, governability, governance, and governmentality.